Erratum: OKANISHI, M. & FUJITA, T. (2011) Two new species of the subgenus Asteroporpa (Astromoana) (Ophiuroidea: Euryalida: Gorgonocephalidae) from Japan. Zootaxa, 2751, 25–39. - Okanishi, M.; Fujita, T. (Zootaxa, 2011)
(Erratum)